(3HZjI GdWGdH aj eYQaI GdeaQhV hGdhGLHs - (3GdLfGMj, GdfLaj, GdeGdcj, LYaQ Hf NVQ cGTa GdZWGA, J (B1226(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj CSS bhGYO GdCMcGe(B...(3hHYO abO SCdfj LeY ef GdCJbjGA(B... (3Cf CcJH dge QSGdI eMJhjI Ydi CUhd GdhGLHGJ hEjVGM eG GaJQVg Gddg ef GdYHGOGJ hGdGYJbGOGJs
(3BNQgG (B:s
(3aaj hLhH NQhLgG Edi GdefRd ddGYJOGO hhLhH GYJOGOgG aj GdeSLO eOI GdGYJcGa bhdGfs
(3JHUQI GdYfhGf (B:s
(3aj EjVGM Gdecfhf(B: (3ZfjI GdWGdHs
(3JHUQI GdeDda (B:s
(3aj SfI haGJg GNJdGa(B: 1228(3, h(B: 1227(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B491s
Keywords: (3abg GdePGgH GdCNQis